2005
DOI: 10.1007/s10709-005-4916-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Wild Rice Oryza Glumaepatula Populations in Three Brazilian Biomes Using Microsatellite Markers

Abstract: The existence of Oryza glumaepatula is threatened by devastation and, thus, the implementation of conservation strategies is extremely relevant. This study aimed to characterize the genetic variability and estimate population parameters of 30 O. glumaepatula populations from three Brazilian biomes using 10 microsatellite markers. The levels of allelic variability for the SSR loci presented a mean of 10.3 alleles per locus and a value of 0.10 for the average allelic frequency value. The expected total heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
5
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 31 publications
8
45
5
8
Order By: Relevance
“…The average apparent outcrossing rate is in agreement with the estimate obtained by Brondani et al (2005) for O. glumaepatula, namely t a = 0.135. The low t a estimate found in our study is a consequence of the high intrapopulation coefficient of inbreeding detected (average f = 0.750, Table 4).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The average apparent outcrossing rate is in agreement with the estimate obtained by Brondani et al (2005) for O. glumaepatula, namely t a = 0.135. The low t a estimate found in our study is a consequence of the high intrapopulation coefficient of inbreeding detected (average f = 0.750, Table 4).…”
Section: Resultssupporting
confidence: 89%
“…These indices were superior to those reported by Buso et al (1998) (H o = 0.00 to 0.025 and H e = 0.00 to 0.21) and Akimoto et al (1998) (H o = 0.03 and H e = 0.044) with isozyme markers, probably due to the high degree of heterozygosity and higher allele number detected by the microsatellite markers in our study. However, Brondani et al (2005) found lower values for these indices (H o = 0.027 Karasawa et al 405 and H e = 0.113) with O. glumaepatula populations investigated using microsatellite markers (Table 7). The difference between our results and those of Brondani et al could be due to both the higher number of plants per population sampled in our study (an average of 27.4 in our study compared to 13.8 by Brondani et al) and also to the greater number of Amazon biome populations sampled by us.…”
Section: Genetic Variationmentioning
confidence: 83%
See 3 more Smart Citations